2020
DOI: 10.5194/bg-17-5919-2020
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical impact of cable bacteria on coastal Black Sea sediment

Abstract: Abstract. Cable bacteria can strongly alter sediment biogeochemistry. Here, we used laboratory incubations to determine the potential impact of their activity on the cycling of iron (Fe), phosphorus (P) and sulfur (S). Microsensor depth profiles of oxygen, sulfide and pH in combination with electric potential profiling and fluorescence in situ hybridisation (FISH) analyses showed a rapid development (<5 d) of cable bacteria, followed by a long period of activity (>200 d). During most of the experiment, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…Cable bacteria grow as long multicellular filaments and act as centimetre‐scale electrical conductors in aquatic sediments, providing a conduit for rapid electron transport from deeper sulfidogenic horizons up to an oxic sediment surface (Nielsen et al, 2010 ). Since their discovery about a decade ago (Pfeffer et al, 2012 ), cable bacteria have been observed in a wide range of depositional sedimentary environments (Aller et al, 2019 ; Burdorf et al, 2016 ; Hermans et al, 2020 ; Scholz et al, 2021 ), and frequently at high cell densities (Malkin et al, 2017 ). Especially where these bacteria achieve high biomass, their metabolic activity can drive intense localized changes in pH and strongly influence the cycling of oxygen, sulfur, iron, manganese, phosphorus, carbonate, organic carbon, and trace metals (Huo et al, 2022 ; Rao et al, 2016 ; Risgaard‐Petersen et al, 2012 ; Sulu‐Gambari et al, 2016a , 2016b ; van de Velde et al, 2016 ), with impacts on the ecosystem level (Seitaj et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cable bacteria grow as long multicellular filaments and act as centimetre‐scale electrical conductors in aquatic sediments, providing a conduit for rapid electron transport from deeper sulfidogenic horizons up to an oxic sediment surface (Nielsen et al, 2010 ). Since their discovery about a decade ago (Pfeffer et al, 2012 ), cable bacteria have been observed in a wide range of depositional sedimentary environments (Aller et al, 2019 ; Burdorf et al, 2016 ; Hermans et al, 2020 ; Scholz et al, 2021 ), and frequently at high cell densities (Malkin et al, 2017 ). Especially where these bacteria achieve high biomass, their metabolic activity can drive intense localized changes in pH and strongly influence the cycling of oxygen, sulfur, iron, manganese, phosphorus, carbonate, organic carbon, and trace metals (Huo et al, 2022 ; Rao et al, 2016 ; Risgaard‐Petersen et al, 2012 ; Sulu‐Gambari et al, 2016a , 2016b ; van de Velde et al, 2016 ), with impacts on the ecosystem level (Seitaj et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the strong redox gradients at the water-sediment interface and potentially high iron and sulfate found in Delta soils [68] suggests that other microbial-mediated P release pathways may be occurring. For example, cable bacteria and Beggiatoacaea bacteria are known mediators of P release from sediments through the enhanced formation of iron and sulfur oxides [69].…”
Section: However Nomentioning
confidence: 99%
“…When the bottom water turns anoxic, this iron firewall captures the sulfide diffusing upward and this can prevent/delay the escape of sulfide from the sediment over a period of weeks ( Seitaj et al, 2015 ). In doing so, the detrimental effects of hypoxia and euxinia, both in the benthic and pelagic environments, are alleviated naturally ( Marzocchi et al, 2018 ; Hermans et al, 2020 ). The reduction of sulfide levels in sediments by e-SOx likely favors the growth of seagrass and mussel beds, and the re-colonization of benthic macro- and meiofauna ( Seitaj et al, 2015 ; Malkin et al, 2017 ; Martin et al, 2018 ; Bonaglia et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%